A simple non-extractive green method for the spectrophotometric sequential injection determination of copper(ii) with novel thiazolylazo dyes. Issue 29 (30th April 2018) - Bazel, Y.; Tupys, A.; Ostapiuk, Y.; Tymoshuk, O.; Imrich, J.; Šandrejová, J.
Abstract : A facile sequential method for the determination of copper(ii ) in tap and river waters with high sample throughput is proposed. Abstract : This work introduces two new thiazolylazo dyes 1-[(5-benzyl-1, 3-thiazol-2-yl)diazenyl]naphthalene-2-ol (BnTAN) and 1-[5-(4-sulfonamidobenzyl-4-methyl-1, 3-thiazol-2-yl)diazenyl]naphthalen-2-ol (SABnMeTAN) as possible reagents for spectrophotometric determination of copper(ii ) in water samples in the form of a chelate complex. The substances were synthesized for the first time and characterized using the NMR technique. The main characteristics of ligands, such as molar absorption coefficients and protonation constants, were evaluated spectrophotometrically. A non-extractive sequential injection spectrophotometric method for the determination of copper(ii ) in the presence of Triton X-100 was developed. The linear range of the calibration plot was observed from 0.063 to 1.270 mg L −1 and the detection limit was 0.044 mg L −1 . The SIA method was compared with the respective manual method and applied for the determination of copper(ii ) in tap and river water.